Peran Strategi Komunikasi Dalam Meningkatkan Efektivitas Organisasi Di Era Digital (Kajian Teori Dan Praktik Komunikasi Strategis) - Ayu Putu Widhiawati; Wayan Wastawa (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The rapid development of digital technology has transformed organizational communication into a more complex, dynamic, and interactive process. In this context, communication strategy plays a crucial role in determining organizational success in achieving its goals and maintaining relationships with stakeholders. This study aims to analyze the role of communication strategy in enhancing organizational effectiveness in the digital era, identify communication challenges, and formulate adaptive and sustainable communication strategies. The research uses a qualitative approach with a library research method by analyzing scientific literature indexed in national (SINTA) and international journals. The findings show that well-planned, participatory, and digitally integrated communication strategies can improve coordination, strengthen organizational image, and enhance stakeholder trust. However, challenges such as information overload, miscommunication, and digital communication crises remain significant obstacles. Therefore, organizations need to develop flexible, transparent, and responsive communication strategies to adapt to environmental changes.